Biochemical abnormalities in neonatal seizures in term and preterm neonates - D., Manoj; K., Rajesh Reddy; Prakash, S. S. (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal seizures may arise as a result of diverse etiologies and can have varied presentations. Biochemical abnormalities are commonly observed in neonates which can be either primary or secondary. Early recognition and treatment of biochemical disturbances is essential for optimal management and satisfactory long-term outcome. Methods: A total of 100 neonates presenting with seizures admitted to NICU of JJM Medical College, Davanagere, from November 2015 to April 2017 were enrolled in the study. Detailed antenatal, natal, postnatal history along with detailed examination was done along with baseline characteristics of convulsing were recorded at admission along with relevant biochemical investigations before instituting any specific treatment. Results: In the present study, out of 100 neonates studied, 64 were full term of which 49(76.5%) were AGA and 15(23.5%) were SGA, whereas 36 cases were preterm. Most neonatal seizures occurred in first 3 days of life, i.e. 59% of which majority occurred on first day of life (34%). Birth asphyxia and septicemia are common cause of neonatal seizures in present study (38 cases each), followed by pure metabolic disturbances 19%. In pure metabolic seizures, hypoglycemia (47.8%) is most common more in preterm babies (55%) followed by hypocalcemia. Conclusions: Biochemical abnormalities are common in neonatal seizures and often go unrecognized and may significantly contribute to seizure activity. Hence, a biochemical work up is necessary for all cases of neonatal seizures.